2016
DOI: 10.14214/sf.1510
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation-related patterns of genetic differentiation in pedunculate oak (<i>Quercus robur</i>) at two hierarchical scales

Abstract: Highlights• While long-lived, widespread tree species should be resistant to genetic impoverishment, we detected high differentiation among populations and pronounced genetic structure within populations of Quercus robur in Finland.• These patterns seem indicative of population processes active at range margins, and of disequilibrium following historic habitat change. • Preservation of remaining genetic variation is thus important in the conservation of Q. robur. AbstractPopulations at species' range margins a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 49 publications
1
13
0
1
Order By: Relevance
“…The breaks between pedunculate oak generations in Russia are 60-80 years. It is possible that the relatively small and fragmented populations in this study are not yet in a stage of serious decreasing genetic diversity due to genetic drift (Pohjanmies et al 2016). Earlier it was noted that genetically effective long-distance pollen flow can be a factor in maintaining relatively similar genetic diversity in these populations (Buschbom et al 2011).…”
Section: Discussionmentioning
confidence: 90%
“…The breaks between pedunculate oak generations in Russia are 60-80 years. It is possible that the relatively small and fragmented populations in this study are not yet in a stage of serious decreasing genetic diversity due to genetic drift (Pohjanmies et al 2016). Earlier it was noted that genetically effective long-distance pollen flow can be a factor in maintaining relatively similar genetic diversity in these populations (Buschbom et al 2011).…”
Section: Discussionmentioning
confidence: 90%
“…We have previously used 15 nuclear microsatellite loci to characterize genetic variation in the study landscape, including the five mother trees included in the current study. These studies revealed substantial genetic variation within the study landscape, with support for two genetic clusters (Pohjanmies et al 2015(Pohjanmies et al , 2016. While the five genotypes are selected from, and reflective of this landscape scale, we do note that the number of genotypes selected are too few to thoroughly represent the genetic variation at the landscape scale.…”
Section: Methodsmentioning
confidence: 93%
“…Quercus species with authors Q. ilex (Michaud et al, 1995) Q. chrysolepis (Montalvo et al, 1997) Q. petraea(1) (Streiff et al, 1998) Q. robur(1) (Streiff et al, 1998) Q. robur(2) (Degen, Streiff, & Ziegenhagen, 1999) Q. suber(1) (Jiménez, Agundez, Alia, & Gil, 1999) Q. petraea(2) (Bruschi, Vendramin, Bussotti, & Grossoni, 2000) Q. pubescens(1) (Bruschi et al, 2000) Q. petraea(3) (Gömöry, Yakovlev, Zhelev, Jedináková, & Paule, 2001) Q. robur(3) (Gömöry et al, 2001) Q. petraea(4) (Mariette, et al, 2002) Q. robur(4) (Mariette et al, 2002) Q. shumardii (Aldrich et al, 2003) Q. palustris (Aldrich et al, 2003) Q. robur(5) (Muir & Schlötterer, 2005) Q. petraea(5) (Muir & Schlötterer, 2005) Q. aquifolioides (Zhang, Korpelainen, & Li, 2006) Q. suber(2) (Lopez-Aljorna, Bueno, Aguinagalde, & Martin, 2007) Q. gemminata(1) (Cavender- Bares & Pahlich, 2009) Q. virginiana(1) (Cavender- Bares & Pahlich, 2009) Q. engelmannii (Ortego, Riordan, Gugger, & Sork, 2012) Q. suber 3 Q. liaotungensis (Wang et al, 2014) Q. lobata (Ashley, Abraham, Backs, & Koenig, 2015) Q. petraea(6) (Curtu, Craciunesc, Enescu, Vidalis & Sofletea, 2015) Q. robur(6) (Curtu et al, 2015) Q. pubescens(2) (Curtu et al, 2015) Q. frainetto (Curtu et al, 2015) Q. robur(7) (Moracho et al, 2016) Q. robur(8) (Pohjanmies et al, 2016) Q. rubra (Sullivan, Owusu, Weber, Hipp, & Gailing, 2016) Q. ellipsoidalis (Sullivan et al, 2016) Q. coccinea (Sullivan et al, 2016) Q. velutina (Sullivan et al, 2016) Q. infectoria Q. mulleri …”
Section: Miguelmentioning
confidence: 99%